2013
DOI: 10.21273/hortsci.48.8.980
|View full text |Cite
|
Sign up to set email alerts
|

Water Use and Growth of Hibiscus acetosella ‘Panama Red’ Grown with a Soil Moisture Sensor-controlled Irrigation System

Abstract: Efficient water use is becoming increasingly important for horticultural operations to satisfy regulations regarding runoff along with adapting to the decreasing availability of water to agriculture. Generally, best management practices (BMPs) are used to conserve water. However, BMPs do not account for water requirements of plants. Soil moisture sensors can be used along with an automated irrigation system to irrigate when substrate volumetric water content (u) drops below a set threshold, allowing for precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
(29 reference statements)
13
30
0
1
Order By: Relevance
“…Increasing height with increasing q threshold was also reported for Hibiscus acetosella 'Panama Red' (Bayer et al, 2013), Gaura lindheimeri 'Siskiyou Pink' (Burnett and van Iersel, 2008), and Callistemon citrinus 'Firebrand' (Á lvarez and Sánchez-Blanco, 2013). In contrast, Fulcher et al (2012) found that shoot length of Hibiscus rosa-sinensis 'Cashmere Wind' was greatest for intermediate treatments rather than high or low q treatments.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…Increasing height with increasing q threshold was also reported for Hibiscus acetosella 'Panama Red' (Bayer et al, 2013), Gaura lindheimeri 'Siskiyou Pink' (Burnett and van Iersel, 2008), and Callistemon citrinus 'Firebrand' (Á lvarez and Sánchez-Blanco, 2013). In contrast, Fulcher et al (2012) found that shoot length of Hibiscus rosa-sinensis 'Cashmere Wind' was greatest for intermediate treatments rather than high or low q treatments.…”
Section: Resultsmentioning
confidence: 67%
“…Increasing shoot dry weight with increasing q thresholds has been reported for Gaura lindheimeri 'Siskiyou Pink' (Burnett and van Iersel, 2008) and Hibiscus acetosella 'Panama Red' (Bayer et al, 2013) with salable plants produced at moderate thresholds (0.25 to 0.35 m 3 · m -3 and 0.35 to 0.40 m 3 · m -3 , respectively). Reduced irrigation volumes have been used to produce plants with minimal reductions in plant growth.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations